Development Of Sekaa Selonding Manik Selukat Banjar Tunjuk Kelod | Pembinaan Sekaa Selonding Manik Selukat Banjar Tunjuk Kelod - I Wayan Yoko Mahase Putra (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Selonding is a traditional Balinese musical instrument older than other gamelans, which is now widespread in art and traditional and religious ceremonies. The word Selonding is thought to have come from the words